Data-driven healthcare : how analytics and BI are transforming the industry - Madsen, Laura B., 1973- (John Wiley and Sons, Inc., 2014)
Data is revolutionizing the healthcare industry. With more data available than ever before, and applying the right analytics you can spur growth. Benefits extend to patients, providers, and board members, and the technology can make centralized patient management a reality. Despite the potential for growth, many in the industry and government are questioning the value of data in health care, wondering if it's worth the investment. This book tackles the issue and proves why BI is not only worth it, but necessary for industry advancement. Madsen challenges the notion that data has little value in healthcare, and shows how BI can ease regulatory reporting pressures and streamline the entire system as it evolves. She illustrates how a data-driven organization is created, and how it can transform the industry. --